Pengaruh Good Corporate Governance dan Ukuran Perusahaan Terhadap Nilai Perusahaan: Kinerja Keuangan Sebagai Variabel Intervening (Studi pada perusahaan sektor keuangan yang terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Siti Miftahul Jannah; Farahiyah Sartika (Universitas Islam Lamongan, 2022)
The purpose of this study is to see whether there is an effect of the implementation of good corporate governance, firm size, and financial performance on firm value. And the results are known if the implementation of good corporate governance has a positive effect on firm value, in contrast to firm size and financial performance which have a negative effect on firm value. On the one hand, financial performance can be an intervention variable for good corporate governance and firm size on firm value in a positive direction. From these objectives and results, it is recommended for further researchers to explore the indicators that exist in each member to find out valid findings by reviewing various aspects.